Assessment of n-pentanol additive and EGR rates effects on spray characteristics, energy distribution and engine performance. (15th December 2019) - Huang, Haozhong; Guo, Xiaoyu; Huang, Rong; Li, Junqi; Pan, Mingzhang; Chen, Yingjie; Pan, Xuezhi
Highlights: Optical diagnostic method was used to analyze n -pentanol blends spray process. The addition of n -pentanol improved the atomization of the blended fuels. The combination of n -pentanol and EGR reduced soot-NOX emissions simultaneously. Adding n -pentanol could reduce the energy loss of Soot and THC emissions. The addition of n -pentanol to biodiesel/diesel blends reduced the PM emissions. Abstract: Owing to the high viscosity of biodiesel, it is not suitable for atomization and volatilization, and it has limitations in reducing emissions. As an alternative fuel with high oxygen content, n -pentanol mixed with biodiesel can reduce viscosity and improve volatility. Therefore, in this work, assessment of n -pentanol additive and EGR rates effects on spray characteristics, energy distribution and engine performance were investigated. The test fuels were pure diesel (D100), a mixture of 20% biodiesel and 80% diesel (BD20), and 20% n -pentanol, 16% biodiesel, and 64% diesel (BDP20). The results indicated that the addition of n -pentanol shortened the liquid phase penetration (LPP) of the mixed fuel and decreased the liquid phase spray cone angle (SCA); at the same time, the addition of n -pentanol could reduce the total particle mass concentration (TPMC) and the total particle number concentration (TPNC), and also reduce the energy loss of Soot and THC emissions, while the brake thermal efficiency (BTE) was not much different from D100 and BD20; further, with the EGR rate increased, the peak of the heat release rate (HRR) of BDP20 increased, and the trade-off relationship between NOx-Soot was improved.